Stunting and Factors Affecting Toddlers in Indonesia - Devi Artanti, Guspri; Fidesrinur; Garzia, Meyke (Jurnal Pendidikan Usia Dini, 2022)
ABSTRACT: Asia is the second region after Africa to have the tallest prevalence of stunting in the world. Indonesia is one of the countries in Southeast Asia with the fifth highest prevalence of stunting in the world at 37%, or nearly 9 million children who experience stunting. This study aims to examine the factors that influence and risk the occurrence of stunting in children in Indonesia. The research method uses a type of qualitative research with a traditional literature review. This study found that stunting is influenced by several complex factors not only at the individual level but also at the family and community levels. A comprehensive synthesis of the available evidence on the determinants of stunting in children in Indonesia outlines who is most vulnerable to stunting, which interventions are successful, and what new research is needed to fill knowledge gaps. Keywords: Indonesian toddlers, stunting factors References: Adair, L. S., & Guilkey, D. K. (1997). Age-specific Determinants of Stunting in Filipino Children. The Journal of Nutrition, 127(2), 314–320. https://doi.org/10.1093/jn/127.2.314 Akombi, B. J., Agho, K. E., Hall, J. J., Merom, D., Astell-Burt, T., & Renzaho, A. M. N. (2017). Stunting and Severe Stunting Among Children Under-5 Years in Nigeria: A Multilevel Analysis. BMC Pediatrics, 17(1), 1–16. https://doi.org/10.1186/s12887-016-0770-z Asfaw, M., Wondaferash, M., Taha, M., & Dube, L. (2015). Prevalence of Undernutrition and Associated Factors Among Children Aged Between Six to Fifty Nine Months in Bule Hora District, South Ethiopia. BMC Public Health,15(1), 41. https://doi.org/10.1186/s12889-015-1370-9 Badan Penelitian dan Pengembangan Kesehatan. (2018). Hasil Utama RISKESDAS 2018. Bardosono, S., Sastroamidjojo, S., & Lukito, W. (2007). Determinants of Child Malnutrition During the 1999 Economic Crisis in Selected Poor Areas of Indonesia. Asia Pacific Journal of Clinical Nutrition, 16(3), 512–526. Best, C. M., Sun, K., De Pee, S., Sari, M., Bloem, M. W., & Semba, R. D. (2008). Paternal Smoking and Increased Risk of Child Malnutrition Among Families in Rural Indonesia. Tobacco Control, 17(1), 38–45. https://doi.org/10.1136/tc.2007.020875 Biadgilign, S., Shumetie, A., & Yesigat, H. (2016). Does Economic Growth Reduce Childhood Undernutrition in Ethiopia? PLoS ONE, 11(8), 1–14. https://doi.org/10.1371/journal.pone.0160050 Black, R. E., Victoria, C. G., Walker, S. P., Bhutta, Z. A., Christian, P., Onis, M. de, Ezzati, M., McGregor, S. G., Katz, J., Martorell, R., Uauy, R., & The Maternal and Child Nutrition Study Group. (2013). Maternal and Child Undernutrition and Overweight in Low-income and Middle-income Countries. The Lancet, 382, 396. Budge, S., Parker, A. H., Hutchings, P. T., & Garbutt, C. (2019). Environmental Enteric Dysfunction and Child Stunting. Nutrition Reviews, 77(4), 240–253. https://doi.org/10.1093/nutrit/nuy068 Burchi, F. (2010). Child Nutrition in Mozambique in 2003: The Role of Mother’s Schooling and Nutrition Knowledge. Economics and Human Biology, 8(3), 331–345. https://doi.org/10.1016/j.ehb.2010.05.010 Casale, D., Espi, G., & Norris, S. A. (2018). Estimating the pathways through which maternal education affects stunting: Evidence from an urban cohort in South Africa. 21(10), 1810–1818. https://doi.org/10.1017/S1368980018000125 Casanovas, M. del C., Lutter, C. K., Mangasaryan, N., Mwadime, R., Hajeebhoy, N., Aguilar, A. M., Kopp, C., Rico, L., Ibiett, G., Andia, D., & Onyango, A. W. (2013). Multi-sectoral Intervensions for Healthy Growth. Matern Child Nutrition, 2, 46–57. https://doi.org/10.1111/mcn.12082 Chirande, L., Charwe, D., Mbwana, H., Victor, R., Kimboka, S., Issaka, A. I., Baines, S. K., Dibley, M. J., & Agho, K. E. (2015). Determinants of Stunting and Severe Stunting Among Under-Fives in Tanzania: Evidence from The 2010 Cross-sectional Household Survey. BMC Pediatrics, 15(1), 1–13. https://doi.org/10.1186/s12887-015-0482-9 Creswell, J. W. (2014). A Concise Introduction to Mixed Methods Research. SAGE Publications Inc. Dao, D., Thang, V. Van, & Hoa, D. T. (2010). Malnutrition Status and Related Factors Within Ethnic Minority Children Under 5 Years Old in North Tra My District, Quang Nam Province in 2010. Journal of Science, 61. Fantay Gebru, K., Mekonnen Haileselassie, W., Haftom Temesgen, A., Oumer Seid, A., & Afework Mulugeta, B. (2019). Determinants of Stunting Among Under-Five Children in Ethiopia: A Multilevel Mixed-Effects Analysis of 2016 Ethiopian Demographic and Health Survey Data. BMC Pediatrics, 19(1), 1–13. https://doi.org/10.1186/s12887-019-1545-0 Fitri, L. (2018). Hubungan BBLR dan ASI Eksklusif Dengan Kejadian Stunting di Puskesmas Lima Puluh Pekanbaru. Jurnal Endurance, 3(1), 131–137. Goldstein, H. (2010). Multilevel Statistical Models, 4th Edition. Wiley. Handayani, F., Siagian, A., & Aritonang, E. (2017). Mother’s Education as A Determinant of Stunting among Children of Age 24 to 59 Months in North Sumatera Province of Indonesia. IOSR Journal of Humanities and Social Science, 22, 58–64. https://doi.org/10.9790/0837-2206095864 Hendraswari, C. A., Purnamaningrum, Y. E., Maryani, T., Widyastuti, Y., & Harith, S. (2021). The Determinants of Stunting for Children Aged 24-59 Months in Kulon Progo District 2019. Kesmas: Jurnal Kesehatan Masyarakat Nasional, 16(2), 71–77. https://doi.org/10.21109/kesmas.v16i2.3305 Hoddinott, J., Alderman, H., Behrman, J. R., Haddad, L., & Horton, S. (2013). The Economic Rationale For Investing In Stunting Reduction. Maternal & Child Nutrition, 9, 69–82. https://doi.org/10.1111/mcn.12080 Horrell, S., Humphries, J., & Voth, H.-J. (2001). Destined for Deprivation: Human Capital Formation and Intergenerational Poverty in Nineteenth-Century England. Explorations in Economic History, 38(3), 339–365. https://doi.org/10.1006/exeh.2000.0765 International Food Policy Research Institute. (2016). Global Nutrition Report 2016: From Premise to Impact: Ending Malnutrition by 2030. Kementerian Kesehatan Republik Indonesia. (2016). InfoDATIN: Situasi Balita Pendek. Kementerian Kesehatan Republik Indonesia. (2018). Warta KESMAS: Cegah Stunting itu Penting. Kimani-Murage, E. W., Muthuri, S. K., Oti, S. O., Mutua, M. K., Van De Vijver, S., & Kyobutungi, C. (2015). Evidence of A Double Burden of Malnutrition in Urban Poor Settings in Nairobi, Kenya. PLoS ONE, 10(6), 1–17. https://doi.org/10.1371/journal.pone.0129943 Kusumawati, E., Rahardjo, S., & Sari, H. P. (2015). Model Pengendalian Faktor Risiko Stunting pada Anak Usia di Bawah Tiga Tahun Model of Stunting Risk Factor Control among Children under Three Years. Kesmas: Jurnal Kesehatan Masyarakat Nasional, 9, 249–256. Madan, E. M., Haas, J. D., Menon, Purnima., & Gillespie, Stuart. (2018). Seasonal Variation In The Proximal Determinants Of Undernutrition During The First 1000 Days Of Life In Rural South Asia: A Comprehensive Review.Global Food Security, 19, 11–23. https://doi.org/10.1016/j.gfs.2018.08.008 McGregor, S. G., Cheung, Y. B., Cueto, S., Glewwe, P., Ritcher, L., Strupp, B., & International Child Development Steering Group. (2007). Developmental Potential in The First 5 Years for Children in Developing Countries. The Lancet, 369, 60–70. https://doi.org/10.1016/S0140-6736(07)60032-4 Mugianti, S., Mulyadi, A., Anam, A. K., & Najah, Z. L. (2018). Faktor Penyebab Anak Stunting Usia 25-60 Bulan di Kecamatan Sukorejo Kota Blitar. Jurnal Ners Dan Kebidanan (Journal of Ners and Midwifery), 5(3), 268–278. https://doi.org/10.26699/jnk.v5i3.art.p268-278 Ntenda, P. A. M., & Chuang, Y.-C. (2018). Analysis of Individual-level and Community-level Effects on Childhood Undernutrition in Malawi. Pediatr Neonatol, 59(4), 380–389. https://doi.org/10.1016/j.pedneo.2017.11.019 Oddo, V. M., Rah, J. H., Semba, R. D., Sun, K., Akhter, N., Sari, M., De Pee, S., Moench-Pfanner, R., Bloem, M., & Kraemer, K. (2012). Predictors of Maternal and Child Double Burden of Malnutrition in Rural Indonesia and Bangladesh. American Journal of Clinical Nutrition, 95(4), 951–958. https://doi.org/10.3945/ajcn.111.026070 Prado, E. L., & Dewey, K. G. (2014). Nutrition and brain development in early life. Nutrition Reviews, 72(4), 267–284. https://doi.org/10.1111/nure.12102 Prakhasita, R. C. (2019). Hubungan Pola Pemberian Makan Dengan Kejadian Stunting Pada Balita Usia 12-59 Bulan di Wilayah Kerja Puskesmas Wedi Surabaya. Universitas Airlangga. Reynaldo, Martorell., & Young, M. F. (2012). Patterns of Stunting and Wasting: Potential Explanatory Factors. Advances in Nutrition, 3(2), 227–233. https://doi.org/10.3945/an.111.001107 Rosiyati, E., Pratiwi, E. A. D., Poristinawati, I., Rahmawati, E., Nurbayani, R., Lestari, S., Wardani, P. S., & Nugroho, M. R. (2019). Determinants of Stunting Children (0-59 Months) in Some Countries in Southeast Asia. Jurnal Kesehatan Komunitas, 4(3), 88–94. https://doi.org/10.25311/keskom.vol4.iss3.262 Sari, M., De Pee, S., Bloem, M. W., Sun, K., Thorne-Lyman, A. L., Moench-Pfanner, R., Akhter, N., Kraemer, K., & Semba, R. D. (2010). Higher Household Expenditure on Animal-Source and Nongrain Foods Lowers the Risk of Stunting Among Children 0-59 Months Old in Indonesia: Implications of Rising Food Prices. Journal of Nutrition, 140(1), 195–200. https://doi.org/10.3945/jn.109.110858 Satriawan, E. (2018). Strategi Nasional Percepatan Pencegahan Stunting 2018-2024. [National Strategy for the Acceleration of Stunting Prevention] Semba, R. D., Kalm, L. M., De Pee, S., Ricks, M. O., Sari, M., & Bloem, M. W. (2007). Paternal Smoking is Associated with Increased Risk of Child Malnutrition Among Poor Urban Families in Indonesia. Public Health Nutrition, 10(1), 7–15. https://doi.org/10.1017/S136898000722292X Semba, R. D., Moench-Pfanner, R., Sun, K., De Pee, S., Akhter, N., Rah, J. H., Campbell, A. A., Badham, J., Bloem, M. W., & Kraemer, K. (2011). Consumption of Micronutrient-fortified Milk and Noodles is Associated with Lower Risk of Stunting in Preschool-Aged Children in Indonesia. Food and Nutrition Bulletin, 32(4), 347–353. https://doi.org/10.1177/156482651103200406 Shieh, S. J., Chen, H. L., Liu, F. C., Liou, C. C., Lin, Y. in H., Tseng, H. I., & Wang, R. H. (2010). The Effectiveness of Structured Discharge Education on Maternal Confidence, Caring Knowledge, and Growth of Premature Newborns. Journal of Clinical Nursing, 19(23–24), 3307–3313. https://doi.org/10.1111/j.1365-2702.2010.03382.x Stewart, C. P., Iannotti, L., Dewey, K. G., Michaelsen, K. F., & Onyango, A. W. (2013). Contextualising Complementary Feeding in a Broader Framework for Stunting Prevention. Matern Child Nutrition, 9(2), 27–45. https://doi.org/10.1111/mcn.12088 Tim Nasional Percepatan Penanggulangan Kemiskinan. (2017). 100 Kabupaten/Kota Prioritas Untuk Intervensi Anak Kerdil (Stunting). Titaley, C. R., Ariawan, I., Hapsari, D., Muasyaroh, A., & Dibley, M. J. (2013). Determinants of the Stunting of Children in Indonesia: A Multilevel Analysis of the 2013 Indonesia Basic Health Survey. Nutrients, 11, 1160. UNICEF. (2015a). UNICEF’ s Approach to Scaling Up Nutrition for Mothers and Their Children. Programme Division, February 9. UNICEF. (2015b). UNICEF’s Approach to Scalling Up Nutrition For Mothers and Their Children. UNICEF. (2018). Progress For Every Child in The SDG Era. United Nations. (2021). United Nations Sustainable Development Goal 2: Zero Hunger. https://sdgs.un.org/goals/goal2 United Nations Children’s Fund. (2013). Improving Child Nutrition: The Achievable Imperative for Global Progress. Worku, B. N., Abessa, T. G., Wondafrash, M., Vanvuchelen, M., Bruckers, L., & Kolsteren, P. (2018). The Relationship of Undernutrition/Psychosocial Factors and Developmental Outcomes of Children in Extreme Poverty in Ethiopia. BMC Pediatrics, 18(1), 1–9. http://dx.doi.org/10.1186/s12887-018-1009-y World Bank Group. (2016). World Development Report 2016: Digital Dividends. World Health Organization. (2010). Nutrition Landscape Information System (NLIS) Country Profile Indicators: Interpretation Guide. World Health Organization. (2012). The Sixty Fifth World Health Assembly: Maternal, Infant, and Young Child Nutrition. World Health Organization. (2014). Global Nutrition Targets 2025: Stunting Policy Brief (No.WHO/NMH/NHD/14.3).